Ecosystem Responses to Holocene Climate Variability Through the Analysis of High-resolution Lake Sediment Cores from Southwestern Québec, Canada - Neil, Karen (Université d'Ottawa / University of Ottawa, 2018)
Lake biotic responses to natural climate variability, fire disturbances, and human impacts over the Holocene were studied at two proximate sites in southwestern Québec. Sediments from Lac Noir and Lac Brûlé had annually deposited laminations (varves), enabling for the precise dating of continuous time-series and high-resolution analysis of subfossil diatom assemblages. The Lac Noir (45°46’31”N, 75°8’23”W, 176 m a.s.l.) record spanned ~11000 years of the Holocene. Stratigraphic changes in diatom assemblages of the lake could be divided into early, mid-, and late periods, broadly paralleling Milankovitch-scale climate intervals and vegetation changes inferred from regional palynological records. The early Holocene (11.1-8.0 ka) climate was cooler and dry, vegetation in the region was comprised of Picea-dominated woodlands, and the lake diatom flora included primarily benthic taxa. Warming in the mid-Holocene (8.0-3.6 ka) allowed for stabilization of soils and forests in the catchment, stronger thermal stratification in the lake, and resultant increases in oligo-mesotrophic diatom taxa such as Discostella stelligera. During the late Holocene (3.6 ka to present), an increase in the abundance of deciduous trees (e.g. Betula and Alnus) in response to cooling led to nutrient-enrichment and higher overall lake productivity. The record from Lac Brûlé (45°43’09”N, 75°26’32”W, 270 m a.s.l.) encompassed the last ~1200 years of the late Holocene. Generalized additive models (GAM) revealed a tight coupling between diatoms and catchment-mediated processes (e.g. vegetation and disturbances), which were closely aligned with climate variations. During the Medieval Warm Period (800-1300 CE), pollen-based inferences of warmer summer temperatures were associated with high abundances of Cyclotella bodanica var. intermedia and Cyclotella rossii; this signalled oligotrophic lake conditions and prolonged thermal stratification. The onset of the Little Ice Age (1450-1850 CE) marked a cooling in the region, and a decline in Tabellaria flocculosa str. IIIp indicated increased nutrient loading from the catchment area. Situated less than 300m from Lac Brûlé are remnants of the Wallingford-Back Mine, which ran from 1924-1972 CE; activities at the mine resulted in local changes to nutrient availability and primary productivity at this site. In previous studies of both Lac Noir and Lac Brûlé, pollen records had indicated overall similarities in the vegetation histories in response to climate variability during the late Holocene. Diatom assemblages were influenced by individual lake conditions and were thus unique to each site; nevertheless, they were closely linked with local and regional patterns of vegetation composition. A main point of difference in the paleo-records from both lakes was attributed to a local fire in the Lac Brûlé catchment at 1345 CE, which caused an early decline in hemlock (Tsuga). The decrease in hemlock was seen at Lac Noir only centuries later, and diatoms in each lake responded according to vegetation changes within their own respective catchments. This research shows that high-resolution sampling of lake sediments is able to detect diatom responses to both long-term and abrupt changes in the environment. Individual sites show similarly timed responses of other proxy-indicators, such as pollen and cladocera, to climate and land-use changes. However, distinct differences in the aquatic biota of well-dated proximate sites can be used to identify influences of regional climate variations, which are sometimes masked by localized, non-climatic processes.
Keywords: Diatoms; Paleolimnology; Little Ice Age; Medieval Warm Period; Varve; Holocene